English as a Foreign Language Students' Emotional Intelligence Management When Taking Speaking Exams - Sara Bata; Cristal Castro (Universidad Nacional de Colombia, 2021)
This article is a mixed method study which examines how a group of six elementary students who study English as a foreign language manage their emotional intelligence while taking their speaking exams. Data were collected through both quantitative and qualitative instruments such as an emotional intelligence test, non-participant observations, surveys, and individual interviews with open-ended questions. The results provide further insight into the students' emotional intelligence and the coping mechanisms/strategies used to manage their emotional intelligence while taking two different speaking exams.